2018
DOI: 10.30972/vet.2923277
|View full text |Cite
|
Sign up to set email alerts
|

Efectos de un herbicida a base de glifosato sobre hematíes de Prochilodus lineatus (Pisces, Prochilodontidae)

Abstract: En la actualidad el sistema agrícola tiene como principal propósito el aumento de la producción con el fin de garantizar el abastecimiento y distribución de sus productos en el mercado, sea interno o externo, generando así mayor rentabilidad económica. Esto trae aparejado la implementación de diferentes agroquímicos que, vertidos al ambiente, pueden tener un impacto negativo sobre la flora, fauna, cuerpos hídricos e incluso en seres humanos. El glifosato (Roundup Full II) es uno de los herbicidas más empleados… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…In the epidermis and dermis, it was common to nd vacuolation as hyaline drops in the cytoplasm of the basal cells. This cytoplasmic vacuolation could be a non-speci c sign of tissue alteration and a mechanism of the organism to reduce the harmful effect of xenobiotic (Cooley et al, 2000;Sarkar et al, 2005;Caramello et al, 2018). Moreover, the presence of mitochondria exhibiting a matrix with different electron densities and the presence of electron-dense granules in the dermis, hypodermis, and muscle tissue, suggests that the Roundup Active® promoted physiological alterations in the organism as a mechanism to repair cellular damage in adaptation to the contaminated environment (Strilbyska et al, 2022) An increase in the thickness of the dermis was observed due to excretory structures, while in some amphibian species these structures are related to serous glands, in D. molitor it was possible to observe three types of glands; serous, mucous, and granular, the last two characterized by the condensation of some granules without substructures and with a major electron-dense content (Brunetti et al, 2012).…”
Section: Ultrastructural Effectsmentioning
confidence: 99%
“…In the epidermis and dermis, it was common to nd vacuolation as hyaline drops in the cytoplasm of the basal cells. This cytoplasmic vacuolation could be a non-speci c sign of tissue alteration and a mechanism of the organism to reduce the harmful effect of xenobiotic (Cooley et al, 2000;Sarkar et al, 2005;Caramello et al, 2018). Moreover, the presence of mitochondria exhibiting a matrix with different electron densities and the presence of electron-dense granules in the dermis, hypodermis, and muscle tissue, suggests that the Roundup Active® promoted physiological alterations in the organism as a mechanism to repair cellular damage in adaptation to the contaminated environment (Strilbyska et al, 2022) An increase in the thickness of the dermis was observed due to excretory structures, while in some amphibian species these structures are related to serous glands, in D. molitor it was possible to observe three types of glands; serous, mucous, and granular, the last two characterized by the condensation of some granules without substructures and with a major electron-dense content (Brunetti et al, 2012).…”
Section: Ultrastructural Effectsmentioning
confidence: 99%